The use of new pedagogical methods on the topic of geography of inexhaustible and Renewable Natural Resources of the geography of the 10th grade - Obidjonov Asadbek Hikmatillo Ogli; Arabboyev Asliddin Rafikzhan Ogli (Genius Journals, 2023)
Interactive methods are ways in which students are taught by a teacher based on the demand of the Times. This article gives a number of methods on the use of new pedagogical methods (“correct confusion”, “Insert”, “finish sentence”) on the topic of the geography of inexhaustible and Renewable Natural Resources of the 10th grade. As a result of the use of these methods, it serves to strengthen both theoretical and practical knowledge of schoolchildren.
Keywords: pedagogy; pedagogical technology; didactics